Harmonizing STEM with Arts: Crafting an Innovative Physics Electronic Module on Vibration and Wave Concepts - Yuberti Yuberti; Vandan Wiliyanti; Antika Febriyani (Jurnal Pembelajaran Fisika, 2023)
Art provides a unique lens through which to explore scientific phenomena, allowing students to visualize complex ideas and express their understanding in imaginative ways. Moreover, the combination of STEM and art, which we call STEAM, encourages holistic learning experiences. This study aims to develop STEAM-based electronic modules for physics learning, focusing on the Vibrations and Waves concept, and to assess the feasibility and attractiveness of this developed electronic module. This research follows a research and development (R&D) approach, employing a 3D development model (Define, Design, and Develop). The study was conducted at MTsN 1 Bandar Lampung, involving eighth-grade students as research participants. The research object was a STEAM-based electronic module on Vibrations and Waves material. Validation results were obtained from both media and subject matter experts, with both categories indicating a very high level of validation, signifying that the electronic module successfully meets the criteria for development based on media and subject matter. Furthermore, the results from development trials involving teachers and students indicated that the electronic module was highly attractive. Consequently, this study concludes that the developed electronic module is highly feasible as teaching material and is very attractive to use by teachers and students.Keywords: Electronic module, Vibration and waves, Development, STEAMDOI: http://dx.doi.org/10.23960/jpf.v11.n2.202303